The Relationship Between Nurses’ Job Stress and The Implementation of Patient Safety in The Hospital - Kustriyani, Menik; Mariyati, Mariyati (University of Muhammadiyah Semarang, 2020)
Nurses’ job stress is considered as a human resource management’s issue in the hospital. Study literature reviewed 13.6% of ICU nurses encounter the potential threat related to the patient safety occurrences. This study was designed to investigate the correlation between nurses’ job stress and the implementation of patient safety in the hospital in-patient room. This study used a quantitative-analytical method with a cross-sectional approach. A total of 30 respondents were recruited by using proportionate random sampling. A self-reported questionnaire was utilized to collect the data. The normality data was tested by using Kolmogorov Smirnov analysis (p<0.05). Spearman Rank test was applied to analyze the overall data. The study findings revealed there was no significant relationship between nurses’ job stress and the patient safety on the target 1 (implementation of patient identification), target 3 (drug safety improvement), target 4 (definitive location and procedure of surgery patient), target 5 (post-health-services infection risk) and target 6 (risk-falls reduction). However, the analysis was found to be statistically significant between nurses’ job stress and effective-communication enhancement (target 2 of patient safety). The study findings concluded that stress could positively impact to improve nurses’ awareness to maintain the 6 targets of patient safety